2009
DOI: 10.1002/pssa.200880485
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic diamond films as a platform material for label‐free protein sensors

Abstract: In the framework of developing a fast and label‐free immunosensor for C‐reactive protein (CRP) detection, H‐terminated nanocrystalline diamond (NCD) was functionalised with anti‐CRP antibodies that were physically adsorbed to the surface. Impedance spectroscopy was used to electronically detect real‐time CRP recognition. Different impedance behaviours were observed after CRP addition as compared to after FITC‐labelled ssDNA addition at low (100 Hz) as well as at high frequencies (1 MHz). Physical interpretatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
(34 reference statements)
0
18
0
Order By: Relevance
“…Recently several studies demonstrated that these particles are completely innocuous and will remain in cytoplasm after sub-cultured for several passages [23,26,27]. Another advantage of nanocrystalline diamond is accessible functionalization by different bio-molecules such as DNA or antibodies for various biosensor applications [28]. Furthermore, we recently showed UNCD films could be used as a biomaterial for enhancing the proliferation and differentiation of NSCs [29].…”
Section: Introductionmentioning
confidence: 98%
“…Recently several studies demonstrated that these particles are completely innocuous and will remain in cytoplasm after sub-cultured for several passages [23,26,27]. Another advantage of nanocrystalline diamond is accessible functionalization by different bio-molecules such as DNA or antibodies for various biosensor applications [28]. Furthermore, we recently showed UNCD films could be used as a biomaterial for enhancing the proliferation and differentiation of NSCs [29].…”
Section: Introductionmentioning
confidence: 98%
“…This initial interaction is then followed by multipoint interactions due to various degrees of protein denaturation, making desorption from the surface extremely difficult (Silin, V et al, 1997). The experiments of our group indicated that the biological activity of the antibodies was not hampered (Bijnens et al, 2009). …”
Section: Antibodiesmentioning
confidence: 97%
“…A Au wire in contact with the reaction fluid served as a counter electrode. The selective antigen recognition was analyzed in real-time, and the detection limit was found to be 10 nM, which was in the physiologically relevant range, and could be discriminated within 10 minutes (Bijnens et al, 2009). Tran et al (2011) described an impedimetric aptasensor for the detection of human IgE.…”
Section: Impedimetric Immunosensorsmentioning
confidence: 99%
“…44 In addition, diamond is being considered for use in neural prostheses. Arrays of solution-gate fi eld-effect transistors were fabricated by Dankerl et al using hydrogen-terminated single-crystalline diamond substrates.…”
Section: Diamond-based Medical Devicesmentioning
confidence: 99%